Author Correction: Light Intensity-dependent Variation in Defect Contributions to Charge Transport and Recombination in a Planar MAPbI3 Perovskite Solar Cell (Scientific Reports, (2019), 9, 1, (19846), 10.1038/s41598-019-56338-6) - Ryu, Shinyoung; Nguyen, Duc Cuong; Ha, Na Young; Park, Hui Joon; Ahn, Y. H.; Park, Ji Yong; Lee, Soonil (Scientific Reports, 2020)
A glitch in the authors’ reference-management software led to extensive errors in the reference list and in-text citations. These errors have been corrected in the PDF and HTML versions of the Article.